2021
DOI: 10.1021/acs.chemrev.0c01140
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-Based Detection of Circulating Targets for Precision Medicine

Abstract: The past decade has witnessed ongoing progress in precision medicine to improve human health. As an emerging diagnostic technique, liquid biopsy can provide realtime, comprehensive, dynamic physiological and pathological information in a noninvasive manner, opening a new window for precision medicine. Liquid biopsy depends on the sensitive and reliable detection of circulating targets (e.g., cells, extracellular vesicles, proteins, microRNAs) from body fluids, the performance of which is largely governed by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
258
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(258 citation statements)
references
References 603 publications
0
258
0
Order By: Relevance
“…Among them, the stability of DNA aptamers was much higher than that of RNA due to its chemical property. However, to overcome this dilemma, a wealth of synthetic chemical method has been introduced into the SELEX and post-SELEX modification process to improve the stability of aptamers [ 15 ]. For example, 2′-fluoro-, 2′-amino-, and 2′-O-methyl-substituted libraries modification make the aptamers more stable in biological application.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the stability of DNA aptamers was much higher than that of RNA due to its chemical property. However, to overcome this dilemma, a wealth of synthetic chemical method has been introduced into the SELEX and post-SELEX modification process to improve the stability of aptamers [ 15 ]. For example, 2′-fluoro-, 2′-amino-, and 2′-O-methyl-substituted libraries modification make the aptamers more stable in biological application.…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary studies of our group showed that circulating miRNAs could be applied in the screening of BC patients, as we identi ed four plasma miRNAs and four serum miRNAs from the miR-106a-363 cluster, which could be used as new noninvasive biomarkers for BC detection [11]. Continuous liquid biopsies can indicate the dynamic evolution of tumor, re ect heterogeneity, assess the variance of different metastatic lesions, observe the effect of treatment on tumor cells and monitor clonal evolution, which would promote understanding the mechanisms of chemoresistance and provide precise and individualized treatment plans in refractory tumors [12][13][14][15][16][17]. We have explored the use of circulating miRNAs as prognostic markers for NCT, and identi ed miR-1275 was signi cantly associated to the response to NCT as well as the correlation to OS in LABC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of C-miRNA can distinguish healthy patients from disease patients. In addition, C-miRNA helps to identify tumor origin and classify tumor types and subtypes, which are important for cancer diagnosis, treatment and prognosis Similarly, the detection of C-miRNA still has some problems, such as expensive equipment and complex operation, which still needs further exploration [ 14 ].…”
Section: Detection Of Exosome Mirnamentioning
confidence: 99%